A Descriptive-Comparative Study of Implementation and Performance of Family Physician Program in Iran and Selected Countries - Bita SEPEHRI; Reza GHAFFARI; Alireza JEDDIAN; Fariba SALEK; Robabeh EMROUZI; Saeideh GHAFFARIFAR; Flora BAGHBAN REZVAN (Iranian Journal of Public Health, 2020)
Background: The implementation of Family Physician Program (FPP) in Iran during the past decade, despite of its numerous achievements, has faced many challenges. We aimed to compare the implementation and the performance of FPP in Iran with selected countries, in order to analyze those challenges and suggest potential solutions.